Process-induced food toxicants : occurance,formation,mitigation, and health risks - Stadler, Richard H.; Lineback, David R. (Wiley, 2009)
Combines the analytical, health, and risk management issues relating to the processing-induced toxins that may be present in common foods. This book considers the different processing methods used in the manufacture of foods, including thermal treatment, drying, fermentation, preservation, fat processing, and high hydrostatic pressure processing